Comparative analysis of indixes of intestinal parasites, evaluated in two different stages, in the village of Matinha dos Pretos, Feira de Santana, Bahia, Brazil - Araújo, Bruno S. de; Santos, João F. dos; Oliveira, Alany S.; Neiva, Tahise da S. (SITIENTIBUS série Ciências Biológicas, 2007)
The Laboratory of Clinical Analyses at UEFS carried out a study of identification of anemias and intestinal parasites in the village of Matinha dos Pretos, Feira de Santana - BA in 2000. This showed high levels of intestinal parasites (68.52%), particularly of ancilostomatids (Ancylostomatidae, Ancylostoma) (57.14%). After five years, the same laboratory executed a review on the indexes of parasites on this population aiming at updating data for this region. Fecal material was once again collected end parasitological exams were carried out. The methods used were Spontaneous Sedimentation or Lutz’s Method and Baermann-Moraes Method. Out of 699 samples analysed 62.52% presented intestinal parasites, and individuals between the ages of 7-18 years old presented the highest indexes. Moreover, 46% of these had evidenced a parasitism polished with up to the six types of different species. The most frequent parasites were ancilostomatids and Entamoeba histolytica Schaudim with percentile values of 74.83% and 13.76% respectively. The results observed prove that the maintenance of the level of intestinal parasites in the population is related to the transmission form, life conditions and hygiene of the population.